The Effect of Promotions and Pricing on the Decision to Stay at Mori Hotels in Kuala Simpang - Ria, Chainar Elli; Marbun, Sondang Ni Bulan; Purba, Alimin; Fauzan K, Khairil; Afnina, Afnina (Journal Of Accounting Management Business And International Research, 2023)
This research was conducted to determine the effect of promotion and pricing on the decision to stay at the Mori Hotel in Kuala Simpang. The sampling technique used was purposive sampling, namely selecting the sample to be the respondent was everyone who was found and stayed at the Mori Kuala Simpang Hotel, aged 21 years and over because they were considered to have been able to make rational decisions and be able to represent all visitors. The distribution of the questionnaire started from 15 to 30 June 2022 with a total of 52 people. The results showed that the factor that dominates the decision to stay at the Mori Hotel in Kuala Simpang is the promotion factor 0.396. This is indicated by the regression value being greater than the pricing factor -0.052. Obtained a value of 25.1%, the decision to stay is influenced by promotions and pricing. The remaining 74.9% is influenced by other factors not recorded in this study. Other factors are thought to be competitors' price factors, demographics, changes in buying habits, tastes and so on.